Exploring the Impact of Assessment as Learning on EFL Learners' Writing Performance: A Study of Varying Levels of Writing Engagement - Fitriyah, Ima; Widiati, Utami; Maboa, Rachel Mmapitso; Ningrum, Ary Setya Budhi (JOLLT Journal of Languages and Language Teaching, 2026)
In English as a Foreign Language (EFL) higher education, writing ability requires effective assessment. This study investigates the effect of Assessment as Learning (AaL) on students' argumentative writing performance. While AaL has been recognized for improving writing, limited research has explored its effects in relation to students' writing engagement (WE). This study examines (a) whether students taught through AaL perform better in writing than those given teacher feedback, (b) whether different WE level lead to different performance outcomes, and (c) whether there is an interaction between assessment type and WE level. Using a quasi-experimental 2x2 factorial design, the study involved two fourth-semester classes at an Islamic university in Kediri, Indonesia. One class (15 students) received AaL, while the other (13 students) received teacher feedback over 12 sessions. The AaL group followed Lee’s (2016) framework, incorporating personal goals, writing criteria, descriptive feedback, self- and peer assessment, and learning logs. Writing performance was measured through pre- and post-tests assessed by two raters, and WE levels were determined using a 27-item Writing Engagement Scale. Results from a two-way ANOVA showed a significant effect of AaL on students' writing performance. However, WE level and their interaction with the assessment method did not significantly affect outcomes. The findings suggest that AaL, particularly when adapted through Lee’s principles, enhances writing performance regardless of WE level. While engagement may not be the primary determinant of the success of AaL, EFL instruction could utilize AaL to enhance students writing outcomes and engagement in the classroom.